A case report of paratesticular rhabdomyosarcoma management: Orchiectomy, pre-radiation testicular transposition, and post-radiation orchiopexy - Morgan R. Sturgis; Jennifer Rosen; Edward M. Gong; Emilie K. Johnson (Urology Case Reports, 2025)
Paratesticular rhabdomyosarcoma is a rare malignancy with favorable prognosis when treated with radical inguinal orchiectomy ± chemotherapy and radiation for patients with advanced disease. When scrotal radiation is indicated, testicular preservation is a pivotal consideration. A widely accepted recommendation is temporary transposition of the remaining testicle to a thigh pouch prior to initiation of radiation. Here, we describe the clinical course of a young patient with paratesticular rhabdomyosarcoma and our unique operative approach using a Bianchi incision during thigh pouch creation to allow for groin preservation followed by a staged inguinal approach for post-radiation orchiopexy.